Molecular-level characterization of supraglacial dissolved and water-extractable organic matter along a hydrological flow path in a Greenland Ice Sheet micro-catchment - E. L. Doting; E. L. Doting; I. T. Stevens; A. M. Kellerman; P. E. Rossel; R. Antony; R. Antony; A. M. McKenna; A. M. McKenna; M. Tranter; L. G. Benning; L. G. Benning; et al. (Biogeosciences)
Sunlight penetrates the bare-ice surface of glaciers and ice sheets, giving rise to the presence of a three-dimensional porous matrix of partially melted ice crystals known as the weathering crust. Surface meltwater slowly percolates through this weathering crust, which hosts active and diverse bacterial communities, until it reaches a supraglacial stream. Despite the potential implications of weathering crust dynamics for glacial melting and the export of carbon and nutrients to downstream ecosystems, its role in biogeochemical cycling remains unknown. Here, we use Fourier transform cyclotron resonance mass spectrometry to characterize dissolved organic matter (DOM) along a meltwater flow path in a hydrologically connected micro-catchment on the southern Greenland Ice Sheet. We find a decrease in the relative abundance of aromatic formulae from surface ice (24.9 ± 2.8 %) to weathering crust meltwater (3.5 ± 0.3 %) to supraglacial stream water (2.2 ± 0.2 %), pointing towards photodegradation of aromatic DOM during supraglacial meltwater transit. The relative abundance of aliphatic and peptide-like formulae in supraglacial stream DOM was lower (38.5 ± 4.0 %) than in weathering crust meltwater DOM (50.3 ± 2.4 %), likely as a result of microbial respiration of labile compounds within the weathering crust. Hence, we conclude that the weathering crust plays a thus far unexplored role in supraglacial biogeochemical cycling. In addition, we characterize water-extractable organic matter isolated from surface ice particulate matter, which was predominantly (61.6 ± 8.1 % relative abundance) comprised of aliphatic and peptide-like formulae, providing the first direct evidence of surface ice particulate matter as a potential source of biolabile DOM. As the spatial extent of bare-ice surfaces and the associated weathering crust photic zone is set to increase under a warming climate, our findings underscore the pressing need to further evaluate the role of the weathering crust in supraglacial biogeochemical processes. An understanding of weathering crust biogeochemical cycling is especially critical as climatic warming is predicted to lead to an increase in Arctic rainfall, consequently increasing the frequency of weathering crust degradation events, with unknown impacts on the export of supraglacial DOM to downstream ecosystems.